Physical fitness and wellness changing the way you look, feel and perform - Greenberg, Jerrold S.; Dintiman, George B.; Myers Oakes, Barbee (Human Kinetics, 2004)
This comprehensive text aims to provide students with the information, strategies & motivation they need to help themselves improve the way they look, feel & perform